TRANSKULTURASI MUSIK ANTARAGAMELAN JAWA, ANGKLUNG, DAN MUSIK TRADISI THAILAND - Surasak Jamnongsarn (Pascasarjana Institut Seni Indonesia Padang Panjang, 2019)
Javanese gamelan and angklung to Thailand music gives the impact on the development of Thailand traditional music. That musical transculturation exists in the musical instrument of angklung and the musical concept of Javanese gamelan that are then mixed with the system of Thailand traditional music involving gamut (tuning system), presentment method, and its function in society. This transculturation shows the understanding of cultural relation between Thailand traditional music that has the background of Buddhism philosophy and Gamelan that has the background of Kejawen syncretism. These two kinds of music have formed the new characteristic and identity of Thailand music. Angklung played with the concept of Javanese gamelan called as angklung Thailand that then becomes Thailand traditional music. The article aims at revealing the transculturation of Javanese gamelan and angklung into the traditional music and its impact on the development of Thailand traditional music. This research used qualitative method with the accentuation in field research that involved researcher with the material object to delve various musical experiences by participating as the player of those two musical instruments. The transculturation of Javanese gamelan and angklung with Thailand traditional music has given the new development in Thailand traditional music. Keywords: Transculturation, Javanese gamelan, angklung, and Thailand traditional music ABSTRAKTranskulturasi gamelan Jawa dan angklung ke Thailand memberikan dampak pada perkembangan musik tradisi Thailand. Transkulturasi musik itu berwujud pada alat musik angklung dan konsep musikal gamelan Jawa, kemudian bercampur dengan sistem musik tradisi Thailand, yang mencakup pada tangga nada (tuning system), carapenyajian, dan fungsinya dalam masyarakat. Transkulturasi inimemunculkan pemahaman relasi kebudayaan antara musik tradisi Thailand yang berlatar belakang filosofi Buddhisme dan gamelan yang berlatar belakang sinkretis kejawen. Kedua musik ini telahmembentuk ciri dan identitas baru musik Thailand.Angklung yang dimainkan dengan konsep gamelan Jawa yang disebut angklung Thailand selanjutnya menjadi musik tradisi Thailand. Artikel bertujuan mengungkap transkulturasi gamelan Jawa dan angklung ke musik tradisi serta dampaknya pada perkembangan musik tradisi Thailand. Penelitian ini menggunakan metode kualitatif dengan penekanan pada penelitian lapangan yang melibatkan peneliti dengan objek materialuntuk menggali berbagai pengalaman musikal dengan ikut serta bermain kedua musik itu. Transkulturasi gamelan Jawa dan angklung dengan music tradisi Thailand telah memberikan perkembangan baru pada musik tradisi Thailand. Kata kunci: transkulturasi, gamelan Jawa, angklung, dan musik tradisi Thailand